Penguatan Daya Saing Perkebunan Kelapa Sawit Swadaya Melalui Pelatihan Manajemen Biaya Dan Integrasi Peternakan Di Kecamatan Muara Kelingi - Verry Yarda Ningsih; Ririn Novita (Universitas Dehasen Bengkulu, 2026)
Muara Kelingi District is one of the main centers for oil palm plantations in Musi Rawas Regency, South Sumatra. The area of smallholder oil palm plantations in this region reaches around 15,720 hectares, with most already producing. Smallholder oil palm farmers' dependence on chemical fertilizers and fluctuations in FFB prices are the main challenges for economic sustainability in Muara Kelingi. This community service program aims to improve farmers' competitiveness through cost management training and introducing the oil palm-livestock integration system (SISKA). The method used is Participatory Technology Development (PTD) through socialization, unit cost calculation training, and waste utilization demonstrations. The results show an increase in farmers' understanding of managing plantation cash flow and potential fertilizer cost efficiency of up to 30% through livestock integration. This program contributes to sustainably improving farmers' productivity and welfare.